A global emerging disease of Klebsiella pneumoniae liver abscess: is serotype K1 an important factor for complicated endophthalmitis?. Issue 3 (1st March 2002) - Fung, C-P; Chang, F-Y; Lee, S-C; Hu, B-S; Kuo, B I-T; Liu, C-Y; Ho, M; Siu, L K
Abstract : Background and aims: Over the past two decades in Taiwan, pyogenic liver abscess has usually been caused by a single microorganism, Klebsiella pneumoniae, and is frequently associated with the serious complication of endophthalmitis, especially in diabetic patients. However, the relationship between the clinical presentation and bacterial factors remains unclear. The aim of this study was to investigate the clinical features of patients and the serotype and ribotype of K pneumoniae liver abscess. Methods: From July 1991 to June 1998, a total of 134 cases of K pneumoniae liver abscess with 248 K pneumoniae isolates from the same patients were collected from two large medical centres in northern Taiwan. Clinical data were collected from medical records. Serotyping and ribotyping were performed using the countercurrent immunoelectrophoresis method and automated Riboprinter. Results: Serotyping revealed that the most common serotypes were K1 (63.4%) and K2 (14.2%). K1 isolates occurred at a significantly higher frequency (p<0.01) than all other serotypes. Among 134 patients, 105 (78.4%) had suffered from diabetes mellitus for 3–15 years. Fourteen patients (10.4%) had metastatic infection to the eye causing septic endophthalmitis. Liver aspirates, and blood and vitreous pus cultures yielded the same serotype of K pneumoniae in all patients. Among patients with septic endophthalmitis, 92.3% (13/14) were diabetic, and 85.7% (12/14) of the isolates belonged to serotype K1. For molecular typing, different degrees of genetic polymorphism among isolates with the same K1 serotype suggested no particular prevalence of any one strain in K pneumoniae liver abscess. Conclusion: K pneumoniae serotype K1 was significantly associated with liver abscess and the complication of endophthalmitis, especially in diabetic patients. Physicians should request an immediate report of serotyping and susceptibility test results simultaneously if a diagnosis of pyogenic liver abscess has been made so that early and appropriate management for possible complications will not be delayed. The use of ceftriaxone because of its higher concentration in the aqueous humor is suggested to decrease the chance of septic endophthalmitis.